2022
DOI: 10.1007/s42380-022-00145-7
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review on Primary School Teachers’ Characteristics and Behaviors in Identifying, Preventing, and Reducing Bullying

Abstract: Despite the expanding body of research on school bullying and interventions, knowledge is limited on what teachers should do to identify, prevent, and reduce bullying. This systematic literature review provides an overview of research on the role of primary school teachers with regard to bullying and victimization. A conceptual framework was developed in line with the Theory of Planned Pehavior, which can serve in further research to facilitate research in investigating the prevention and reduction of bullying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 85 publications
0
8
0
Order By: Relevance
“…We also took into account whether teachers worked in primary or secondary education. A recent study found that secondary school teachers reported lower scores on different elements representing school culture (van Aalst, 2022). For that reason, we explored whether some of the effects of our Theory of Planned Behavior framework were differently for teachers working in secondary rather than in primary education.…”
Section: The Current Studymentioning
confidence: 99%
See 3 more Smart Citations
“…We also took into account whether teachers worked in primary or secondary education. A recent study found that secondary school teachers reported lower scores on different elements representing school culture (van Aalst, 2022). For that reason, we explored whether some of the effects of our Theory of Planned Behavior framework were differently for teachers working in secondary rather than in primary education.…”
Section: The Current Studymentioning
confidence: 99%
“…The conceptual framework (van Aalst et al, 2022) was based on a systematic literature review and consisted of three elements that guide human behavior: 1) teachers' attitudes toward behavior (here: anti-bullying attitudes), 2) behavioral control (e.g., teachers' self-efficacy and attribution styles), and 3) the perceived subjective norms of important others (e.g., colleagues, principal). Teachers' attitudes, behavioral control, and subjective norms may influence their likelihood of intervening in bullying situations, resulting, according to the model, in specific strategies to prevent or tackle bullying (e.g., disciplining the bully, working with the group, or ignoring the incident).…”
Section: Theory Of Planned Behavior Explaining Intervening In Bullyin...mentioning
confidence: 99%
See 2 more Smart Citations
“…In a scoping review, Gizzarelli et al (2023) described individual (perceived self-efficacy, perceived seriousness of the bullying incident, sympathy or empathy for the target, teacher's gender, years of teaching, personal experiences with bullying, and orientation) and school factors (bullying prevention, training, school policies, and organisational characteristics) that influence school staff members' responses to bullying incidents. A recent systematic review by Van Aalst et al (2022) intervene in bullying situations (which also affects the actual behaviour and intervention strategies) can be influenced by teachers' knowledge and understanding of bullying, attitudes toward bullying, perceived subjective norms, and self-efficacy. Therefore, it is important to understand the impact of school bullying and how teachers and non-teaching staff members can address the issue effectively.…”
Section: Problem Statementmentioning
confidence: 99%